An integrated management of change system based on process safety management - Pang, Kar Kei (2019)
Highly hazardous industries grow rapidly due to increasing demand towards petroleum made products. Increasing complexity of manufacturing process cause difficulty to acquire a comprehensive view on safety perspective of the entire complex processes, equipment and personnel. Potential of major accident may significantly increase even more when change is implemented. Unplanned change may lead to new hazards emerged which eventually leads towards severe impact in human, property, environment and business reputation. Management of change is an important element in which involves in planning and controlling risk and hazards that comes with proposed change. However, current MOC implementation were lacking in plant due to lacking systematic MOC process and management system which comprises the whole process of MOC into an integrated system. Corresponding to these weaknesses, an integrated MOC management system is aimed to develop in this study. Objectives of this research are, to develop MOC framework, to develop a management system on MOC and to validate management system developed. Method adopted in this study is much similar as Plan-Do-Act-Check (PDCA) concept. “Plan” stage is conducted by conducting literature review and understanding all requirements of PSM regulation towards MOC. “Do” stage is carried out by developing framework and management system. “Check” is adopted to validate developed management system to ensure efficiency and reliability of system towards real process operation. “Act” is done by optimizing management system and framework to ensure fully compliance towards regulation and enhance user friendly on management system. Result of this study are comprised of an overview of MOC process which displayed by a PDCA cycle, a complete MOC process framework with checklist adopted and a MOC management system which act as guidance and documentation software. Validation process conducted has confirmed MOC framework met basic requirements of selected MOC regulation whereas management system is reliable in system documentation and information storage.